Erosive oral lichen planus in an elderly patient: Effect on the quality of life: Case report - Yuli Fatzia Ossa; Anandina Irmagita Soegyanto; Harum Sasanti (Wolters Kluwer Medknow Publications, 2022)
Background: Erosive oral lichen planus (EOLP) causes pain, burning sensation, swelling, and bleeding and can affect the quality of life because of pain and discomfort. Here, we report a case of EOLP in an elderly patient, which decreased the quality of life, and a comprehensive management of the case. Case Report: A 75-year-old woman was referred to the Oral Medicine Department of Dental Hospital, Faculty of Dentistry, Universitas Indonesia, with oral discomfort. She complained of pain during meals for 1 year, which results in weight loss. The patient admitted to the hospital because of psychological stress and hypertension. The clinical examination of the right buccal mucosa showed reticular plaque, and erosive and erythema lesions on the left buccal mucosa and soft palate. The patient was diagnosed with EOLP and treated with a topical corticosteroid and multivitamin, and also was treated for the management of stress. Conclusion: EOLP treatment in the elderly patients has its own challenges, because of chronic disease, affects the quality of life, and requires long-term therapy. Treatment must be comprehensive and must pay attention to the systemic and psychological condition of the patient.